POPULARITY OF E-PAYMENT SYSTEM AMONG THE GOVERNMENT EMPLOYEES - Muhammed Faisal T. (MIRROR, 2018)
Electronic payment system is very popular for payment among the people of India after the last demonetarization policy on 08-nov-2016 and establishment of various payment banks , various online payment and E-Wallet. E-payment is any kind of no cash payment that does not involve paper cheque but for using Debit card, Credit Card, E-Wallet, Mobile Banking and Internet Banking system etc.In an E-Commerce environment payment take in the form of electronically is very relevant. During the initial stage of the E-payment process people may feel insecurity due to unfamiliarity and lack of security but now large number of peoples are using E-payment mode for commercial activities. During the electronic commerce, payment in the mode of Electronically is very comfortable to the people. In most of the cases, you only need to enter your account information. the major drawbacks to electronic payment is identity Theft ,privacy problem and virus attack etc.